Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities, 2021)
This issue of KIU Journal of Humanities touches on Development Administration, Social Psychology, Educational Psychology and Communication Studies. The first part of the Journal addresses issues in Development Administration such as waste management, accountability and transparency, rural development, poverty alleviation, sustainable development goals, anti corruption efforts, rail revolution, nation building, and globalization. One of the papers in this section argues that education has a role in improving the lives of women with attendant benefit to empower and promote gender parity in society. It is therefore suggested that since gender parity is important and the role of women central to socio-economic development, government should enact a policy to ensure quality education become a major block of empowering women at every local government area in Nigeria. The second section which centers on Social Psychology, examines various psychology factors which have impacts on the society, and these include sexual morality among adolescents, parenting styles, career management, youth empowerment, job insecurity; trans-border crimes, mental disorder and corporal punishment. One of these papers reveals that human trafficking has a negative effect on socio economic growth in Nigeria. The paper recommends that government should look into factors necessitating trans-border crimes and take legal actions against offenders. The third section which centers on Educational Psychology highlights various social innovations which have impacts on teaching and learning activities in the society.  One of these papers reveals that the motivation of students that were exposed to m-learning differs from the motivation of students that were not exposed to m-learning. It therefore suggests that m-learning should be integrated into the teaching and learning activities of tertiary institutions in Nigeria. In addition, students and lecturers at the higher level of education should be encouraged to possess m-learning devices and utilize m-learning for teaching and learning exercise. It was likewise recommended that lecturers should collaborate with computer programme designers to design m-learning based virtual classrooms.  In the last section, communications skills in both religious and literary world are examined. It is revealed in one of the papers that Writers of Christian religious tracts in the Nigeria rely on emotional appeals, logical proofs and ethics as means of maintaining interpersonal relation with their readers. Also, they assume the position of divine authority and/or of better informed persons to counsel their readers. This conclusion was drawn after the researcher had critically examined the linguistic strategies and the discourse functions of appeal in eleven Christian religious tracts purposively selected from forty tracts collected from about fifteen churches and ministries in Ondo State, South-western Nigeria. In all, this issue of KIU Journal of Humanities features many empirical and theoretical based articles which can be of great benefit to every reader.